2003
DOI: 10.1095/biolreprod.102.015057
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids and Bovine Interferon-τ Modify Phorbol Ester-Induced Secretion of Prostaglandin F2α and Expression of Prostaglandin Endoperoxide Synthase-2 and Phospholipase-A2 in Bovine Endometrial Cells1

Abstract: Embryonic mortality in cattle may occur because of inadequate inhibition of uterine secretion of prostaglandin (PG) F2alpha mediated by bovine interferon-tau (bIFN-tau). The objectives of the present study were to determine whether polyunsaturated fatty acids inhibit secretion of PGF2alpha from bovine endometrial cells induced by stimulating protein kinase C with phorbol 12,13 dibutyrate (PDBu) and to investigate possible mechanisms of action. Confluent cells were exposed for 24 h to 100 microM of linoleic, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 24 publications
4
65
0
3
Order By: Relevance
“…In the current study, AA was highest in the plasma of animals supplemented with FO and this is consistent with other studies on plasma (Burns et al, 2003) and studies on milk (Mattos et al, 2002). AA is converted to PGH2, the precursor of the other prostaglandins, through the actions of the enzyme PGH synthase (PGHS; Mattos et al, 2003). Despite FO supplementation increasing systemic AA, there is evidence from this laboratory and others (Burns et al, 2003) that a high n-3 PUFA diet can reduce uterine endometrial tissue concentrations of AA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, AA was highest in the plasma of animals supplemented with FO and this is consistent with other studies on plasma (Burns et al, 2003) and studies on milk (Mattos et al, 2002). AA is converted to PGH2, the precursor of the other prostaglandins, through the actions of the enzyme PGH synthase (PGHS; Mattos et al, 2003). Despite FO supplementation increasing systemic AA, there is evidence from this laboratory and others (Burns et al, 2003) that a high n-3 PUFA diet can reduce uterine endometrial tissue concentrations of AA.…”
Section: Discussionsupporting
confidence: 92%
“…Linolenic acid is the parent n-3 PUFA, with some limited elongation to the longer chain n-3 PUFA, EPA and DHA occurring. An in vitro study by Mattos et al (2003) showed linolenic acid to be effective in suppressing PGF 2a from phorbol ester-stimulated bovine endometrial (BEND) cells. Furthermore, cows supplemented with linolenic acid were shown to have had higher concentrations of oestradiol during the follicular phase of the oestrous cycle than unsupplemented cows (Robinson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, PGFM concentrations did not differ by treatment and day, however, the difference observed for percentage change of concentrations of plasma PGFM on days 17 and 18 coincide with the increased plasma concentration of 20:4n-6 observed for FLX. This is in contrast to previous work where increasing the supply of n-3 fatty acids has been shown to decrease prostaglandin metabolite production (Mattos et al, 2003;Petit and Twagiramungu, 2006). The primary differences between the current experiment and published literature is likely the type of cattle used, in that most work with n-3 fatty acids was conducted with dairy-type cattle and various high-quality rations.…”
Section: Discussionmentioning
confidence: 60%
“…An increase in dietary 18:2n-6 will increase prostaglandin F (PGF 2 α) production (Lammoglia et al, 1997;Filley et al, 1999), which may negatively influence embryonic survival (Mattos et al, 2003) owing to decreases in progesterone (Diskin and Niswender, 1989). Progesterone plays a critical role in stimulating production of a variety of endometrial secretions that are necessary for successful embryonic development (Diskin and Morris, 2008).…”
Section: Introductionmentioning
confidence: 99%